Two level dipolar system in a heat bath - Gzyl, Henryk; Paz, José Luis (Ciencia)
Using a theory developed by Fulinsky and Kramarcyk, co bined with weak coupling limit asymptotic perturbative expansion we obtain rate equations for the reduced density matrix of a two level system immersed in a heat bath. PACS: 31.70.Dk; 33.15.Kr.